250 MHZ to 30 GHZ, unilateral circuitmodel for InGaP/GaAs HBT - Thein, Than Tun (2013)
A unilateral circuit model, which precisely predicts small signal response over a wide range of frequencies and bias points, is quantitatively analyzed and presented. The shortfall of current unilateral assumption and transformation technique is presented. A complete and explicit analysis is provided to develop a compact unilateral circuit model. The model is intended to predict input reflection, forward transmission and output reflection coefficients over wide range of frequencies. The technique is validated by transforming bilateral a small signal model of 3 x 3 μm x 40 μm, InGaP/GaAs HBT into its unilateral equivalent over the frequency range of 250 MHz to 30 GHz. The accuracy of the technique is corroborated at various bias conditions; collector current from 3 mA to 150 mA and collector-emitter voltage from 1 V to 5 V. Simulated results show very good agreement between small signal responses of transformed unilateral and bilateral circuit models.